The Future of Globalization Under New Political Realities. (January 2017) - Jara, Alejandro
At a time when many state that globalization is stalled, if not suffering reversals, there are indications that international cooperation on trade issues is alive and can deliver results, provided adequate and timely leadership is exercised. Foreign investment continues to flow, capital markets continue to be global, and trade liberalization continues to take place (not always multilaterally but certainly on a bilateral or plurilateral basis). At the same time, processes of national integration—a sort of national globalization—continue to take place as measures such as the recent national sales tax reform in India, to say nothing of several policies applied in China and elsewhere, all reflect the robust growth of the middle class in emerging economies. Globalization is an endless process that has accelerated and deepened in the last decades and presumably will continue to do so. This implies that the forms and processes of globalization also change. It is therefore very important to have in mind what the drivers of these changes are in order to better understand the necessary adjustments and adaptions. The backlash against globalization is also strong and undeniable. One does not need to go too far to see the political consequences. Different surveys confirm a decline in the support of globalization.